Masa Pandemi Covid-19 Pengabdian Kepada Komunitas Maya - Latifah, Ayu; Priyadi, Rahmat; Hidayatno, Fachrul Ramdaniar; Ramdani, Feri; Irawan, Bambang; Pratama, Novan Noviansyah; Apriliana, Rafli; Rohman, Ripan Reftiana; Endang, Dwi Isyandi; Hilmi, Muhammad Ikhsan (Jurnal PkM MIFTEK, 2022)
The situation of growing Covid-19 cases is very fast in Indonesia. Prevention efforts carried out by the Real Work Lecture team from the Garut College of Technology are one of the solutions in prevention efforts because until now there is no cure for this disease. Prevention that can be done is in the form of socialization by applying cough etiquette and through special protection by using and distributing masks, hand hygiene and social distancing. KKN is a course that is held in semester 4, of course each campus is different. KKN is usually carried out offline by visiting places, especially sub-districts or villages that can be targeted for KKN as areas worthy of assistance, especially in terms of community service. But it's different from this year, with the Covid 19 pandemic, all activities are carried out online due to government policy to limit any activities that cause large crowds. Therefore, this time the Community Service Program is being held online to help the government break the chain of the spread of Covid-19 and at the same time make this course possible even with conditions like this.